Effects of solid-state fermentation and drying on starch properties and flavour of nangka (Musa paradisiaca L., AAB) and tanduk (Musa paradisiaca L. , ABB) plantain flours - Morolayo, Shittu Rafiat (2016)
Plantain plays an important role in the nutritional and economic wellbeing of humans. Nonetheless, plantain is readily susceptible to spoilage due to its high moisture content. Thus, processing plantain to prevent postharvest losses is warranted. The current study examined the effect of solid-state fermentation and drying methods on starch properties and flavor of Nangka and Tanduk plantain flours. The study was conducted in two phases. The first phase of the study appraised the effect of drying methods [Hot air drying (HAD) and Microwave finish drying (MFD)] and solid-state fermentation (SSF) on the physicochemical, functional, physical, rheological and gelatinization properties and aroma compounds of flours of Nangka and Tanduk plantain cultivars. Drying methods and SSF did not affect the fat, dietary fiber and carbohydrate contents of the plantain flours. However, both treatments significantly (p< 0.05) affected the pH and titratable acidity of the flours. In addition, SSF coupled with MFD significantly (p< 0.05) increased the water absorption and oil absorption capacities of the flours more than the flours obtained from the hot air drying. Similar trend was observed with the swelling power and solubility of the flours. The flow behaviour index of all the flour pastes were less than 1 which is an indication of a typical non-Newtonian shear thinning (pseudo plastic) behaviour. The gas chromatography mass spectrophotometry revealed that fermented microwave-finish dried Tanduk plantain flour had 11 (4 alcohols, 1 ketone, 4 esters, 1 sulphur compound and 1 acid) aroma compounds while unfermented microwave-finish dried Tanduk plantain flour had 10 (2 alcohols, 6 acids, and 2 esters) aroma compounds. The fermented microwavefinish dried Nangka plantain flour had 13 (5 alcohols, 2 ester, 2 phenolic compounds, I sulphur compound, 2 acids and 1 sterol) aroma compounds while the unfermented microwave-finish dried Nangka flour had 16 (3 aldehydes, 5 esters, 6 acids and 2 alcohols) aroma compounds. The green pulp of Nangka and Tanduk plantain cultivars subjected to microwave-finish drying and solid-state fermentation produced flour with reduced color degradation and improved functional properties. The second phase of the study assessed the physicochemical, morphological, thermal, textural and functional properties of native starches and starches from fermented microwave finish dried flours of Nangka and Tanduk plantain cultivars. Native and fermented Nangka starches had lower amylose, hardness, cohesiveness, guminess, springiness, and adhesiveness and greater swelling power, solubility, crystallinity, gelatinization temperatures and granular size compared to those of Tanduk. Regardless of cultivar, fermented starches had higher degree of crystalinity, gelatinization properties, and swelling power and solubility but lower amylose content, granular size and textural properties compared with native starches. The X-ray diffraction patterns of fermented and native starches showed an A-type pattern which is rarely reported for plantain starches. The FTIR spectra of the plantain starches present the same characteristic bands in the finger print region of 4000–280 cm-1. The starch granule birefringence did not differ. The scanning electron micrograph revealed that fermented starches had a slightly disrupted and small clustered granules compared with the native starches. Processing conditions influenced the starch properties of Nangka and Tanduk plantain cultivars.